1982
DOI: 10.1172/jci110604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insulin and Glucose on Very Low Density Lipoprotein Triglyceride Secretion by Cultured Rat Hepatocytes

Abstract: A B S T R A C T The effect of insulin on hepatic triglyceride synthesis and secretion is controversial. Previously, we have described a cell culture system of adult rat hepatocytes that synthesize and secrete very low density lipoprotein (VLDL) triglycerides with small and irreproducible effects of insulin on triglyceride metabolism. To study the primary effects of insulin on hepatic triglyceride metabolism a method was developed utilizing fibronectin-coated culture dishes that allowed adhesion, spreading, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
91
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(108 citation statements)
references
References 50 publications
16
91
1
Order By: Relevance
“…This scenario would appear to fit in with the observations (see e.g. [4][5][6][7]) that insulin actually inhibits TAG and apoB secretion by cultured hepatocytes. Consequently, it has been suggested that the prandial increase in portal insulin concentration is sufficient to inhibit VLDL secretion by the liver [8][9][10].…”
Section: Introductionsupporting
confidence: 75%
“…This scenario would appear to fit in with the observations (see e.g. [4][5][6][7]) that insulin actually inhibits TAG and apoB secretion by cultured hepatocytes. Consequently, it has been suggested that the prandial increase in portal insulin concentration is sufficient to inhibit VLDL secretion by the liver [8][9][10].…”
Section: Introductionsupporting
confidence: 75%
“…38 - 40 A further factor that could contribute to the association between increased triglyceride concentrations and insulin resistance could be resistance of adipose tissue lipoh/sis to inhibition by insulin. This and the resistance of glucose elimination to stimulation by insulin may be linked conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whereas experiments conducted with isolated perfused rat liver showed that insulin stimulates both synthesis and secretion of TAG [136,137], many subsequent studies conducted on cultured hepatocytes have found that insulin, although promoting synthesis of TAG, inhibits its secretion [6,8,133,138,139]. The reasons for this discrepancy between the two sets of data may reside in the use of different experimental systems (perfused liver, cultured cells) and in the choice of the precise perfusion or culture conditions, by different laboratories.…”
Section: Experimental Observations For a Role Of Insulin In Tag Secrementioning
confidence: 99%